Spectrum of hemifacial microsomia in a pre-term newborn: case presentation and literature review - Medina de la Cruz, Antonia Yesenia; Rodríguez Balderrama, Isaías; Burciaga Flores, Carlos Horacio; O Cavazos, Manuel Enrique de la (UANL. Facultad de Medicina, 2015)
The spectrum of hemifacial microsomia, or facio-auriculo-vertebral spectrum, is a complex of craniofacial and vertebral anomalies. Axis malformation is microtia, more often on the right side of 3:2. It may be associated with mandibular hypoplasia and vertebral malformations. It is more frequent in males and in twin pregnancies. Clinical case: Newborn male, preterm, of 29.5 weeks gestational age, twin product, second twin pregnancy, dichorionic and diamniotic, born by cesarean section, which presented hemifacial microsomia, microtia of the left Tanzer 3 and the right auricle of low implantation with a backward rotation, left appendices and macrostomia. A thoracoabdominal X-ray found hemivertebrae in the cervical and dorsal area, which discussed genetic performing diagnosis of the hemifacial microsomia spectrum. An ear TAC is done, the bone atresia of the left ear meeting at the level of the left ear without evidence of tympanic membranes and with a dysplastic oscicular chain attached to the lateral wall of the attic. Discharged at 78 days of chronological age with 6 days of age, corrected with the consultation of neonatal high-risk follow-up. Conclusion: Facial asymmetry must be widely evaluated in patients with microtia, including deliberate search of renal, cardiac and spinal-level conditions, in order to diagnose pathologies such as the spectrum of hemifacial microsomia early.